Prerequisites of Research Process - Lulanski, Pano (Research Papers, 2006)
The scientific-research process is productive if only in its organization has been recognized the importance of a number of prerequisites. Among then of great importance are first, the actuality of the theme of the research; second-the choice of adequate research instruments and taxonomy to the chosen object field, and third, availability of a research capacity of the author. In the paper these prerequisites have been analyzed in the context of the elaboration of a qualitative, therefore useful scientific product. Some axiomatic principles of the research work are generalized, too.